A língua portuguesa no barroco: cenas da enunciação e o papel do hiperenunciador em as Cartas espirituais de frei Antonio das Chagas - Celestino, Ricardo (2014)
This dissertation has as its theme the study of scenes of enunciation and the function of hiperenunciator in CartasEspirituais of Frei Antonio das Chagas, written in Portuguese Baroque. Integrated in the line of research text and discourse in oral and written, it is an enunciative-discursive study of social practices of the seventeenth century , grounded by Discourse Analysis of French line, especially the approaches Maingueneau ( 2005, 2006, 2007, 2008a, 2008b, 2011) . We aim to examine the construction of the scenes of enunciation and the function of hiperenunciator in CartasEspirituais, so check how interdiscourse, gender discourse and scenes of enunciation dialogue in discursive function for the emergence of hiperenunciator. The mobility of hiperenunciator is identified by means of the aspects that underlie the different views expressed by the enunciator, recognized from the printed discursive formations in spiritual letters, which constitute a sample for analysis and providing brand of baroque aesthetics and spirituality of the century XVII. Thus, we take the spiritual letters as an institutionalized human activity analysis of religious discourse. The letters are genres of discourse that aim to guide and edify the faithful and religious position of the paradigms of the Catholic Church and of seventeenth-century Christian spirituality. The enunciator, inserted into a social place, enunciatively interacts with a co-enunciator, which also has socio-cultural specificities, in order to convince him that the spiritual guidance has directions, that address the concerns of everyday life. The set of selected letters reveal placements that allow us to consolidate a discursive space of the mean and non- mean. Both the enunciator as co-enunciator faced with sacroprofana controversial religious reforms, enhancement of scientism and decadence of spirituality and seek to position themselves so as not to strike a balance between a position and the other, but to institutionalize itself and defend an absolute truth. Thus, the enunciator assumes a placement in order to invalidate all others, using the rhetoric of gongoric cultism and conceptism also common in Baroque art, to convince the co-enunciator, who meets with faith and devotion institutional shattered front the contradictions of the seventeenth-century world